PENGARUH PENGETAHUAN INVESTASI, PERCEIVED VALUE DAN RISIKO INVESTASI TERHADAP MINAT INVESTASI EMAS DIGITAL PT PEGADAIAN DENPASAR - Kustina, Ketut Tanti; Maulani, Salma (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
Advances in digital technology have significantly changed various aspects of life, including how individuals manage their finances. These technologies drive new lifestyles and create opportunities in the investment landscape. One of the popular investment instruments with low-risk characteristics is gold, which maintains the currency's value with zero inflation characteristics. In this context, PT Pegadaian Denpasar plays an essential role as a financial institution that offers digital gold investment through a reliable and accessible platform. This study aims to analyze the effect of perceived value, investment risk, and investment knowledge on interest in investing in digital gold at PT Pegadaian Denpasar. Using a quantitative approach, 100 respondents were asked to complete a questionnaire to collect primary data. IBM SPSS version 26 was used to analyze the data using multiple linear regression. The results show that interest in investing in digital gold is positively and significantly influenced by perceived value and investment expertise. In contrast, investment risk did not show a significant effect. The conclusion of this study emphasizes the importance of education and increasing the perceived value of digital gold investment to stimulate public interest. The findings from this study can serve as a guide for PT Pegadaian to create a more effective marketing and education strategy plan.